Towards an Adequate Musical Notation of the National Anthem of the Bolivarian Republic of Venezuela (Mayéutica Revista Científica de Humanidades y Artes, 2018)
This article aims to demonstrate that the National Anthem of the Bolivarian Republic of Venezuela has notational deficiencies, mainly in the type of compass used. Certain fundamentals of musical analysis established by different researchers are considered. Some theoretical principles are addressed by the americans Fred Lerdahl and Ray Jackendoff, the Chilean musicologist based in our country Humberto Sagredo Araya, the argentine writers Francisco Kröpfl and María del Carmen Aguilar, and by the Cuban Rolando Antonio Pérez Fernández, among others. Some phenomenal and perceptive aspects are applied to the metric analysis of the National Anthem; among these, the Gestalt laws and the constitutive elements of the metric structure contemplated by the Generative Theory of Tonal Music. Given that our purpose is to establish an effective metric in the emblematic Gloria al Bravo Pueblo and in order to understand this adequacy, we propose a structural comparison with other similar topics. After having studied its characteristics, both accent and notational, we propose a hypermetric notation in the scores and present the conclusions advocating this solution.
Keywords: National Anthem; Bolivarian Republic of Venezuela; metric adaptation; perceptive patterns; musical rhythm